2010
DOI: 10.3892/mmr_00000287
|View full text |Cite
|
Sign up to set email alerts
|

Adrenergic receptor blockade-induced regression of pressure-overload cardiac hypertrophy is associated with inhibition of the calcineurin/NFAT3/GATA4 pathway

Abstract: Abstract. calcineurin and its downstream effectors nuclear factor of activated T-cells 3 (nFaT3) and zinc finger-containing transcription factor (GATA4) have been implicated in the development of cardiac hypertrophy. The aims of the present study were to investigate alterations in the calcineurin/NFAT3/GATA4 pathway in pressure-overload hypertrophy, and to determine whether adrenergic receptor blockade affects this signaling pathway. In aorta-banded rats compared with sham-operated rats, a significant increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…In the present study, abdominal aortic constriction-induced pressure overload resulted in left ventricular myocardial hypertrophy due to the increase in LVW/BW, echocardiography characteristics, cardiomyocyte area and mRNA expression levels of the hypertrophy markers ANF and β-MHC. In pressure overload-induced hypertrophic hearts, phosphorylated activation of Akt, ERK1/2 and GATA4 proteins was significantly increased, which was in agreement with the results of previous studies (11,32,33). Briefly, these results showed that the phosphorylation levels of Akt, ERK1/2 and GATA4 proteins are involved in myocardial hypertrophy induced by abdominal aortic constriction.…”
Section: A B C Dsupporting
confidence: 92%
“…In the present study, abdominal aortic constriction-induced pressure overload resulted in left ventricular myocardial hypertrophy due to the increase in LVW/BW, echocardiography characteristics, cardiomyocyte area and mRNA expression levels of the hypertrophy markers ANF and β-MHC. In pressure overload-induced hypertrophic hearts, phosphorylated activation of Akt, ERK1/2 and GATA4 proteins was significantly increased, which was in agreement with the results of previous studies (11,32,33). Briefly, these results showed that the phosphorylation levels of Akt, ERK1/2 and GATA4 proteins are involved in myocardial hypertrophy induced by abdominal aortic constriction.…”
Section: A B C Dsupporting
confidence: 92%
“…The model is successfully validated in 32 out of 38 (84%) individual hypertrophy experiments, all performed in cardiomyocytes from mice or rats (Alsaad, 2018; Bhavsar et al, 2010; Bombig et al, 1996; Daryadel et al, 2014; Gialama & Maniadakis, 2013; Guan et al, 2019; Lebeche et al, 2001; C. Li et al, 2016; X. Li et al, 2017; Liao et al, 2004; Lin et al, 2015; J. Luo et al, 2016; J.‐D. Luo et al, 2001; Maeno et al, 2000; Morisco et al, 2001; Morishige et al, 2019; Nie et al, 2019; Nkadimeng et al, 2020; Ozakca, 2019; Pacca et al, 2002; Rüdebusch et al, 2022; Samanta et al, 2020; Simpson, 1985; Sysa‐Shah et al, 2012; Takayanagi et al, 2015; Wang, Yao, & Wang, 2010; Yang et al, 2019; Yang et al, 2010; Yin et al, 2016; Yu et al, 2016) (Figure 3a). The model additionally is validated in 28 out of 32 (88%) outcomes from an in vitro drug screen of phenylephrine‐induced cardiomyocyte hypertrophy (Reid et al, 2016) (Figure 3b).…”
Section: Resultsmentioning
confidence: 99%
“…Li et al, 2017;Liao et al, 2004;Lin et al, 2015;J. Luo et al, 2016 Rüdebusch et al, 2022;Samanta et al, 2020;Simpson, 1985;Sysa-Shah et al, 2012;Takayanagi et al, 2015;Wang, Yao, & Wang, 2010;Yang et al, 2019;Yang et al, 2010;Yin et al, 2016;Yu et al, 2016) (Figure 3a). The model additionally is validated in 28 out of 32 (88%) outcomes from an in vitro drug screen of phenylephrineinduced cardiomyocyte hypertrophy (Reid et al, 2016) (Figure 3b).…”
Section: Drugs Modulate Hypertrophy In a Contextdependent Mannermentioning
confidence: 99%
“…NFAT3 is known to be expressed in the heart and has been associated with cardiac hypertrophy [12] . NFAT3 is activated in response to various hypertrophic stimuli, such as mechanical stress [88] and neurohormonal signals [89] . NFAT3 has been implicated in regulating genes that control cell growth [90] , apoptosis [59] , and fibrosis in the heart [91] , all of which are important components of hypertrophic remodelling.…”
Section: Discussionmentioning
confidence: 99%